Consumer Choices: The Influence of Price, Service, and Promotion on Coffee Purchases in Jakarta - Dini Amalia; Rahma Maulidda Witantris; Yopie Yulius (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2025)
The objective of this study was to examine the influence of price, service quality, and promotional efforts on consumer purchasing decisions in Jakarta. The research is grounded in theoretical frameworks that address the relationships between price, service quality, promotion, and purchase decision-making. Primary data served as the basis for this investigation, with the sample selected through purposive sampling techniques. The study’s novelty lies in its focus on the local coffee industry and the application of Smart-PLS software version 4.1.0.9 for data analysis, in contrast to previous research that employed SPSS. Data were gathered via Google Forms from 100 customers of Kopi Sulfan in Central Jakarta. The analysis involved the use of external model evaluation, internal model assessment, and hypothesis testing. The results revealed that price does not significantly affect purchasing decisions, whereas both service quality and promotion exert a positive influence. From a managerial perspective, the findings suggest that business owners should maintain competitive pricing while enhancing service quality and product standards. These improvements are expected to increase the appeal of the business and positively influence consumer purchase decisions. Abstrak - Tujuan penelitian ini yaitu guna menguji apakah terdapat pengaruh harga, kualitas pelayanan, dan promosi terhadap keputusan pembelian di Jakarta. Penelitian berlandaskan teori yang mendukung mengenai harga, kualitas pelayanan, dan promosi terhadap keputusan pembelian. Penelitian ini memanfaatkan data primer, sedangkan sampel diambil dengan metode purposive sampling. Novelty pada penelitian ini berfokus pada sektor usaha kopi lokal dan memanfaatkan perangkat lunak smart-PLS versi 4.1.0.9, sedangkan penelitian sebelumnya menggunakan SPSS. Data dikumpulkan melalui google forms dari pembeli Kopi Sulfan di Jakarta Pusat dengan total 100 responden. Teknik analisis data dilakukan dengan menggunakan model luar, model dalam, dan pengujian hipotesis. Temuan dari pengujian hipotesis membuktikan yakni harga tidak memiliki pengaruh terhadap keputusan pembelian, kualitas pelayanan berpengaruh positif terhadap keputusan pembelian, dan promosi berpengaruh positif terhadap keputusan pembelian. Implikasi dari penelitian ini bagi pemilik usaha perlu mempertahankan harga yang terjangkau bersamaan dengan meningkatkan kualitas dan mutu produknya. Dengan memperbaiki kondisi tersebut diharapkan mampu meningkatkan daya tarik dan mendorong terjadinya pembelian.